Electrochemical Determination of Fenitrothion Organophosphorus Pesticide Using Polyzincon Modified‐glassy Carbon Electrode. Issue 12 (10th October 2017) - Ensafi, Ali Aasghar; Rezaloo, Fatemeh; Rezaei, Behzad
Abstract: In this paper, a glassy carbon electrode (GCE) was modified with polyzincon. The modified electrode was used as a simple, inexpensive and highly sensitive electrochemical sensor for the determination of organophosphorus pesticide fenitrothion. To fabricate the electrochemical sensor, GCE was immersed in 0.10 mmol L −1 zincon solutions at pH 7.0 and then successively scanned between −1.00 to 2.20 V ( vs . Ag/AgCl) at a scan rate of 70 mV s −1 for six cycles. The morphology and structure of the polyzincon were studied with atomic force microscopy and scanning electron microscopy. A comparison of the electrochemical behavior of fenitrothion on the unmodified and polyzincon modified‐GCE showed that in the modified electrode not only the oxidation peak current increased, but also the overpotential shifted to lower one. The experimental conditions such as sample solution pH, accumulation potential, and time were optimized. The differential pulse voltammetric responses of fenitrothion at potential about −0.60 V was used for the determination of fenitrothion. The peak current increased with increasing the concentration of fenitrothion in the range of 5 to 8600 nmol L −1 with a detection limit of 1.5 nmol L −1 . Finally, the electrochemical sensor was used for the analysis of fenitrothion in water and fruit samples. Abstract :